Finding a mathematical disposition instrument of junior high school students in Indonesia - Rosid Bahar; Hidayat, Opik; Syadiah, Ainun Nurul; Sutardi, Budi (Research and Social Study Institute, 2023)
The study aimed to find an instrument for measuring the mathematical disposition of junior high school students in Indonesia. The research type was research and development, which is used to develop instruments of students' mathematical disposition. Data were collected from 384 respondents, who filled out a questionnaire with a total of 7 indicators and 25 statement items. 384 responses were divided into two criteria, stage 1 and stage 2, with each test having 197 respondents. Stage 1 analysis used the Exploratory Factor Analysis (EFA) approach, while stage 2 used the Confirmatory Factor Analysis (CFA) approach. Stage 1 obtained validation of 23 items with a loading factor of more than 0.4, consisting of 1 invalid item and 1 item was not meet expectations. The results of the CFA analysis have proven that 23 items were valid with a loading factor of more than 0.4. The reliability coefficient was 0.59, with an SEM value of 3.98. In sum, this instrument has 23 statements that have fulfilled the validity and reliability of the instrument and were feasible to use.